Targeted Suppression of Chaperone-Mediated Autophagy by miR-320a Promotes α-Synuclein Aggregation - Li, Guobin (MDPI, 2014)
Chaperone-mediated autophagy (CMA) is involved in wild-type α-synuclein degradation in Parkinson’s disease (PD), and LAMP2A and Hsc 70 have recently been indicated to be deregulated by microRNAs. To recognize the regularory role of miR-320a in CMA and the possible role in α-synuclein degradation, in the present study, we examined the targeting and regulating role of miR-320 in Hsc 70 expression. We first constructed an α-synuclein-overexpressed human neuroblastoma cell line, SH-SY5Y-Syn(+), stably over-expressing wild-type α-synuclein and sensitive to an autophagy inhibitor, which exerted no effect on the expression of LAMP2A and Hsc 70. Then we evaluated the influence on the CMA by miR-320a in the SH-SY5Y-Syn(+) cells. It was shown that miR-320a mimics transfection of specifically targeted Hsc 70 and reduced its expression at both mRNA and protein levels, however, the other key CMA molecule, LAMP2A was not regulated by miR-320a. Further, the reduced Hsc 70 attenuated the α-synuclein degradation in the SH-SY5Y-Syn(+) cells, and induced a significantly high level of α-synuclein accumulation. In conclusion, we demonstrate that miR-320a specifically targeted the 3' UTR of Hsc 70, decreased Hsc 70 expression at both protein and mRNA levels in α-synuclein-over-expressed SH-SY5Y cells, and resulted in significant α-synuclein intracellular accumulation. These results imply that miR-320a might be implicated in the α-synuclein aggravation in PD.